A thematic review of neighbourhood built environment factors that affect the sense of community - Azli, Mohd; Abdullah, Jamalunlaili; Abdullah, Yusfida; Sahabuddin, Mohd; Taib, Idris; Shukri, Sharyzee; Abdullah, Azli (Citi University, 2024)
Communities, being vital to human existence, provide members with a sense of identity and purpose. The physical environment of these communities plays a critical role in shaping this sense of belonging, warranting further investigation into this relationship. Despite some research indicating that the built environment influences the local community feeling, the specific aspects and their degree of influence remain largely unknown. This study aims to identify which physical features exert the most impact, and what factors need to be currently addressed. This study conducts a thematic analysis to explore how the built environment of a neighbourhood affects community sentiment, focusing on articles published between 2017 and 2023. The research materials were sourced from the SCOPUS and Web of Science databases based on specific inclusion criteria, with keyword searches yielding 37 peer-reviewed articles. Following a thorough inclusion and exclusion procedure, the final selection of 25 papers was compiled for assessment. Upon conducting a thematic analysis of the 25 selected papers, a total of seventeen physical elements were initially identified. However, so far, only eleven out of these seventeen physical parameters put forth by Kim & Kaplan have been used. These include clubhouses or recreation amenities, population density, the distance between sidewalks and residences, the diversity in types of housing, the overall street layout, lakes, greenways, street trees, landscaping, architectural style, the overall design quality of the residences, and block size. Moreover, it was found that aspects of the neighbourhood are associated with physical activity, satisfaction with the community, a sense of belonging, and the perception of one's position within the neighbourhood. Factors of urban landscape directly impact community contentment, sense of belonging, and perceived quality of life. Physical attributes correlate with levels of physical activity and the sense of community, while aspects of planning and policy are associated with community identity, belonging, and architectural aesthetics influencing the sense of community. The codes presented in this paper elucidate the relationship between a neighbourhood’s-built environment and the sense of community it fosters. The research contributes by examining this category and its variables, pinpointing specific themes within related topics across various publications. This analysis will offer valuable insights for future studies, particularly those focusing on communities within Malaysia.